Design of Web-Based SPP Payment System with Payment Gateway at PAUD Nurul Ikhsan Ciruas Using Laravel Framework - Muhamad Fathin Rizkillah; Umar Mansyuri; Rahadian Arief (Brilliance: Research of Artificial Intelligence, 2025)
The payment process for Education Development Contributions (SPP) at PAUD Nurul Ikhsan Ciruas was previously done manually, which posed challenges in terms of timeliness, accuracy, and transparency in financial recording. These limitations often resulted in delays in payment tracking, difficulties in reporting, and lack of real-time access for parents or guardians. Based on these issues, this study designed and implemented a web-based information system to support both direct and installment payments for SPP. The system includes online payment options through integration with a third-party payment gateway service, namely Midtrans. The development approach adopted in this study followed the Waterfall model, starting from the stages of requirement analysis, system design, implementation, testing, deployment, and maintenance. The resulting application provides several key features such as student data management, automatic invoice generation, installment payment tracking, payment history display, transaction receipt printing, and online payment processing connected to the Midtrans gateway. The results show that the system successfully addresses the problems identified in the manual process by improving the regularity and efficiency of payment administration. Moreover, the system offers better transparency and convenience for users, especially parents or guardians, who can now monitor and complete payments remotely and securely. This innovation contributes to digital transformation in early childhood education institutions.